HISTORY AND DEVELOPMENT DIRECTIONS OF INDUCTION HEATING HFC AT THE MINSK AUTOMOBILE PLANT - P. S. Gurchenko; A. A. Shipko (Литьë и металлургия, 2013)
The data on the development of induction technology in the Republic of Belarus on the example of the Minsk Automobile Plant are given. Their development began at the end of the fifties at the Minsk Tractor Plant, and the highest development has been obtained at the Minsk Automobile Plant from 1983 to 2008. The short features of energy-efficient processes created at MAZ in collaboration with country’s institutions are given: surface hardening on the contour of gear wheels, a body-surface-hardened gears and satellites, the impulse hardening of complex configuration, the heat treatment of long items and bulk materials, etc.Литература